(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Vedas are probably the earliest documents of the human mind and it is indeed difficult to say when the earliest portions of the Vedas came into existence. As the ancient Hindus seldom kept any historical record of their religious, literary and political realizations, it is difficult to determine the period of the Vedas with precision. Historians provide us many guesses but none of them is free from ambiguity."1